STUDI KEBUTUHAN KUANTITAS DAN KUALITAS SDM UNTUK SEKTOR-SEKTOR UNGGULAN DI KAPET SERAM - MALUKU - Elia Radianto (UGM, 2000)
Over the lost a decade, there has been increased attention to the economy of the East-Indonesia Region (KTI), arising particularly from an awareness of the existing serious ambalace in inter-regional development (KAPET) has been adopted to meet and resolve the challenges facing the East-Indonesia Region.